Automated movement recognition to predict motor impairment in high‐risk infants: a systematic review of diagnostic test accuracy and meta‐analysis. (9th January 2021) - Raghuram, Kamini; Orlandi, Silvia; Church, Paige; Chau, Tom; Uleryk, Elizabeth; Pechlivanoglou, Petros; Shah, Vibhuti
Abstract : Aim: To assess the sensitivity and specificity of automated movement recognition in predicting motor impairment in high‐risk infants. Method: We searched MEDLINE, Embase, PsycINFO, CINAHL, Web of Science, and Scopus databases and identified additional studies from the references of relevant studies. We included studies that evaluated automated movement recognition in high‐risk infants to predict motor impairment, including cerebral palsy (CP) and non‐CP motor impairments. Two authors independently assessed studies for inclusion, extracted data, and assessed methodological quality using the Quality Assessment of Diagnostic Accuracy Studies‐2. Meta‐analyses were performed using hierarchical summary receiver operating characteristic models. Results: Of 6536 articles, 13 articles assessing 59 movement variables in 1248 infants under 5 months corrected age were included. Of these, 143 infants had CP. The overall sensitivity and specificity for motor impairment were 0.73 (95% confidence interval [CI] 0.68–0.77) and 0.70 (95% CI 0.65–0.75) respectively. Comparatively, clinical General Movements Assessment (GMA) was found to have sensitivity and specificity of 98% (95% CI 74–100) and 91% (95% CI 83–93) respectively. Sensor‐based technologies had higher specificity (0.88, 95% CI 0.80–0.93). Interpretation: Automated movement recognition technology remains inferior to clinical GMA. The strength of this study is its meta‐analysis to summarize performance, although generalizability of these results is limited by study heterogeneity. What this paper adds: Automated movement recognition is sensitive and specific and warrants further investigation. Sensor‐based technologies have higher specificity but are less portable. The performance of automated movement recognition is inferior to clinical General Movements Assessment. Emerging technologies such as 3D video analysis may improve its performance. What this paper adds: Automated movement recognition is sensitive and specific and warrants further investigation. Sensor‐based technologies have higher specificity but are less portable. The performance of automated movement recognition is inferior to clinical General Movements Assessment. Emerging technologies such as 3D video analysis may improve its performance. Video Podcast: https://youtu.be/mWwQawBf3gU